2020
DOI: 10.3400/avd.cr.20-00094
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Aortoenteric Erosion Due to Pulsatile Stress After Aneurysm Repair: A Case Report

Abstract: Secondary aortoenteric fistula or erosion (SAEFE), an abnormal connection between the aorta and gastrointestinal tract, is a rare but critical complication after abdominal aortic aneurysm repair. Most SAEFEs occur between the aorta or proximal graft anastomosis and the duodenum, and occurrence between the iliac graft and small intestine is rare. Standard SAEFE management involves graft removal and extra-anatomical bypass. However, this is extremely invasive and has a high mortality rate. We encountered a rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…More than 50% of cases had a duration longer than 3 days [ 26 ]. This time frame can be used as an opportunity for the treatment of fistulas [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of cases had a duration longer than 3 days [ 26 ]. This time frame can be used as an opportunity for the treatment of fistulas [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent series [10] demonstrated that SAEF continues to be a life-threatening condition, with a 27% in-hospital mortality rate, which is substantially higher upon emergency presentation, despite prompt diagnosis and treatment. The majority of fistulas involving the intestinal tract are between the aorta and the 3 rd -4 th portion of the duodenum (between the abdominal aorta and the superior mesenteric artery) in 74% of cases, followed by the small intestine (jejunum more commonly than the ileum) 19%, the colon 5%, and the appendix 1% [11][12][13][14].…”
Section: Epidemiologymentioning
confidence: 99%